Analisis Perhitungan Asam Klorida (HCl) Sebagai Pengontrol pH pada Air Cooling Tower pada Pabrik Pembangkit Listrik Tenaga Sampah (PLTSa) - Hernowo Widodo; Rino Dwiatmaja (Jurnal Bhara Petro Energi, 2022)
The Garbage Power Plant (PLTSa) has a water cycle in which heat transfer occurs in the cooling tower. This study looked for the pH level of the hot ratio using samples from hydrochloric acid (HCl) tanks and cooling tower (CT) output water samples. The results obtained by several comparisons of testing and analysis were obtained by 3.6 Liters of adding hydrochloric acid (HCl) to the tank so that the heat transfer that runs on the cooling tower has a pH level of 7. If the pH level is already 7 the possibility for acids or bases to be small and can preventing and maintaining heat transfer flows.process.